ASSOCIATION BETWEEN HYPOMAGNESEMIA AND SERUM LACTATE LEVELS IN PATIENTS WITH SEPSIS - TARIQ , A; ABBAS, MQ; ABBAS, SM; AMJAD, H; ZIA, MH; USMAN, M (Biological and Clinical Sciences Research Journal, 2024)
Sepsis is a critical condition that often leads to systemic inflammation, organ dysfunction, and high mortality rates. It is well known that metabolic abnormalities play a significant role in the pathophysiology of sepsis. Objective: This study aims to investigate the association between hypomagnesemia and serum lactate levels in patients with sepsis, hypothesizing that low magnesium levels may be linked to increased lactate production and worse clinical outcomes. Methods: A retrospective observational study was conducted at Ghurki Trust Teaching Hospital Lahore from January 2024 to June 2024. Data were collected from 255 adult patients diagnosed with sepsis. Patients were divided into two groups based on their serum magnesium levels: those with normal magnesium levels (≥1.7 mg/dL) and those with hypomagnesemia (<1.7 mg/dL). Serum lactate levels were measured within the first 24 hours of ICU admission. Results: Out of the 255 patients, 108 (42.4%) were found to have hypomagnesemia. Patients with hypomagnesemia had significantly higher serum lactate levels compared to those with normal magnesium levels, with mean lactate levels of 4.1 ± 1.2 mmol/L in the hypomagnesemia group versus 2.7 ± 0.9 mmol/L in the normal magnesium group (p < 0.001). Conclusions: This study shows a significant association between hypomagnesemia and elevated serum lactate levels in patients with sepsis.